AI-Powered Legal Documentation Assistant - Imogen, P. Vimala; Sreenidhi, J.; Nivedha, V. (Journal of Artificial Intelligence and Capsule Networks, 2024)
The Legal Documentation Assistant offers a unique method to obtain legal rights, specializing in copyright, trademark, and banking using a combination of artificial intelligence (AI) technologies. Through the synergy of legal expertise and technological innovation, our dynamic website is designed to offer clients real-time assistance and guidance to help them efficiently navigate complex legal requirements. Our personalised bots provide tailored support and answer queries, ensuring clients receive the help they need. At the core of our platform is a combination of AI-powered chatbots designed to provide clients with real-time help and guidance. These bots provide personalized support, answer questions, explain legal concepts and guide customers through multiple procedures. In addition, our platform enables seamless file editing, allowing clients to customize legal templates to suit their needs. By sharing downloadable files in modern formats, we increase the convenience of people even as we sell legal requirements. Through the synergy of legal knowledge and technological innovation, our platform aims to democratize access to empower people and businesses to navigate the methods themselves. We believe that our method is an important step in bridging the gap between legal information and realistic applications.